PENGARUH CITRA MEREK, LOKASI, DAN PROMOSI TERHADAP LOYALITAS KONSUMEN MELALUI MINAT BELI ULANG PADA SALON BEAUTYBARKU DI SITUBONDO - Hamida, Lutfiyatil; Wahyuni, Ika; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The beauty salon industry has experienced rapid growth in this modern era. Grooming and appearance are a primary focus for many individuals, and salons are becoming trendy places to ful fill these needs. Apart from being a plac to care for the body, beauty salons are also considered ideal places to relax and care for. This research aims to analyze the influence of Brand image, Location, and Promotion on consumer Loyalty through Repurchase interest as an intervening variable at the Beautybarku Salon in Situbondo. The number of samples used in this research was 89 Beautybarku respondents in Situbondo. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this research used the Partial Least Square Structural Equation Model (PLS-SEM). The resultsof the direct influence hypothe test using the Smart PLS 3.0 application show that Brand image has a significant positive effect on Repurcha seinterest, Location has a significantly postive effecton Repurchase interest, Promotion has a positive significant effect on Repurchase interest, Brand image has a positive but not significant effecton Loyalty. Consumers, Location has a positive but not significant effect on consumer Loyalty, Promotion has a positive but not significant effect on consumer Loyalty, Repurchase intention has a significant positive effect on Consumer Loyalty. The indirect influence hypothesis test results show that Brand image has a significant positive effecton consumer Loyalty through Repurchase nterest, Location has a positive effect on consumer Loyalty through Repurchase interest, and Promotion has a significant positive effect on consumer Loyalty through Repurchase interest.